From Linear to T‐Shaped Indan‐1, 3‐dione Push–Pull Molecules: A Comparative Study. Issue 8 (9th August 2018) - Solanke, Parmeshwar; Růžička, Aleš; Mikysek, Tomáš; Pytela, Oldřich; Bureš, Filip; Klikar, Milan
Abstract : A series of indan‐1, 3‐dione‐based linear, quadrupolar and T‐shaped push–pull chromophores have been designed and synthesized by the Knoevenagel condensation and Pd‐catalyzed Suzuki–Miyaura or Sonogashira cross‐coupling reactions. The number and position of the peripheral donor branches attached to the central withdrawing indan‐1, 3‐dione moiety have been varied jointly with the type of π ‐linker used in order to modulate fundamental optoelectronic properties. The molecular structure of two chromophores has been confirmed by X‐ray analysis. The thermal and optoelectronic properties have further been investigated by differential scanning calorimetry, electrochemistry, UV/Vis absorption spectroscopy, and DFT calculations. Based on these experimental and theoretical data, thorough structure–property relationships have been further evaluated and influence of the particular structural modification on chromophore properties has been discussed. Abstract :